Design and in vitro cytotoxicity of docetaxel-loaded hyaluronic acid-coated nanostructured lipid carriers in breast cancer cells - Peleje, Isabel Rheinfranck [UNESP]; Di Filippo, Leonardo Delello [UNESP]; Luiz, Marcela Tavares [UNESP]; Fortunato, Giovanna Capaldi [UNESP]; Portuondo, Deivys Leandro [UNESP]; da Silva, Mônica Freitas [UNESP]; Carlos, Iracilda Zeppone [UNESP]; Duarte, Jonatas Lobato [UNESP]; Chorilli, Marlus [UNESP] (Elsevier, 2025)
Breast cancer is one of the most prevalent types of cancer globally. Among the treatment options, docetaxel (DTX) is frequently used as chemotherapy, but its clinical efficacy is limited due to adverse effects and low bioavailability. To minimize toxicity and improve drug delivery to cancer cells, nanostructured lipid carriers (NLC) have been explored. Modifying their surface with hyaluronic acid (HA) can target the drug to CD44 receptors, overexpressed in many cancers like breast cancer, increasing drug accumulation in the target tissue and reducing non-target toxicity. This work aimed to develop and evaluate the in vitro cytotoxicity and cellular uptake of HA-coated NLCs encapsulating docetaxel (HA-NLC-DTX) in breast cancer cells. NLCs were obtained using capric/caprylic acid triglycerides (CCTG) as liquid lipid, glyceryl behenate (Compritol®) as solid lipid, polysorbate 80 (P80) and cetyltrimethylammonium bromide (CTAB) as surfactants, and an aqueous phase composed of ultra-purified water. The HA coating was mediated by electrostatic interactions with a by adding a cationic surfactant (CTAB). The formulations were characterized regarding particle size, polydispersity index (PDI), zeta potential (ZP), encapsulation efficiency, differential scanning calorimetry, infrared spectroscopy, and in vitro release profile. Cytotoxicity was evaluated using the MCF-7 breast adenocarcinoma cell line and L929 cell line. Different formulations were developed varying the proportions of surfactant, solid, and liquid lipid. The particle sizes ranged from 40 nm to 247 nm, with ZP from −23 mV to −8 mV and PDI between 0.27 and 0.76. For CTAB, the concentration of 0.1 % w/v (of total formulation) proved to be the most promising for adding HA, presenting homogeneous particles and lower PDI, which can favor the colloidal stability and optimize drug delivery, showing a positive ZP. Considering the desired colloidal properties, F5 (CCTG 25 mg, Compritol® 35 mg, P80 5 mg, CTAB 1 mg, DTX 1 mg) was selected for subsequent studies. For HA concentrations, 1 mg/ml and 0.5 mg/ml were tested, with ratios ranging from 1:1 to 8:1. Release studies showed a cumulative and controlled release of DTX from NLC, especially HA-coated NLC. In cytotoxicity assays, free DTX showed an IC50 of 91.12 nM after 72 h. The formulation HA-NLC-DTX showed a greater cytotoxic effect than free DTX, with an IC50 of 49.80 nM. Additionally, HA-NLC was successfully internalized by MCF-7 cells as confirmed by flow cytometry. The results confirm that the HA-coated NLC provides a controlled and effective release of DTX, with increased cytotoxicity in breast cancer cells, demonstrating the promising potential of HA-coating in breast cancer-targeted therapies.